2019
DOI: 10.1002/sdtp.13722
|View full text |Cite
|
Sign up to set email alerts
|

P‐15.1: A New Photometric and Colorimetric Measurement Method for RGB Laser Displays

Abstract: The Discrete Centroid Wavelength Method (DCWM) has been newly developed for accurate measurement of the chromaticity and illuminance of laser displays. The accuracy of the new method has been experimentally confirmed by comparing with an optical spectrum analyzer and a calibrated si‐photodiode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The coefficient is 683lm/W so that the tiristimulus value Y is equal to the photometric quantity, and the chromaticity x and y are easily obtained from the tristimulus values [4]. Besides, we also experimentally proved that our DCWM has sufficient accuracy in laser measurement [5]. However, the accurate inspection of chromaticity and photometric quantity is not enough to accelerate the production of laser displays.…”
Section: Introductionmentioning
confidence: 99%
“…The coefficient is 683lm/W so that the tiristimulus value Y is equal to the photometric quantity, and the chromaticity x and y are easily obtained from the tristimulus values [4]. Besides, we also experimentally proved that our DCWM has sufficient accuracy in laser measurement [5]. However, the accurate inspection of chromaticity and photometric quantity is not enough to accelerate the production of laser displays.…”
Section: Introductionmentioning
confidence: 99%
“…In our different study, we reported XYZ-filter illuminance color meters, which have been widely used to test the two parameters of displays in production lines so far, are not accurate enough for laser displays, and we developed a new measurement method named the Discrete Centroid Wavelength Method (DCWM) in order to allow an accurate evaluation of laser displays [2]. Leveraging this new method, we also developed RGB laser meters [3], which can simultaneously measure the centroid wavelength and radiometric quantity of RGB lasers, and proved their accuracy in laser measurement [4]. In addition, ultra short throw laser projectors are positioned very close to a screen, and the incident angle of the light to illuminance meters are very large as shown in Fig.1.…”
Section: Introductionmentioning
confidence: 99%